Pastoral Counseling Strategies for Congregants Experiencing Faith Degradation Due to Secular Digital Content - Johni Hardori; Sabar Halawa; Heru Cahyono (International Perspectives in Christian Education and Philosophy, 2024)
This article examines pastoral counseling strategies for congregants whose Christian faith is weakened by sustained exposure to secular digital content. The problem is not framed as a deterministic claim that digital media directly destroys faith, but as a practical-theological concern: algorithmic personalization, secular moral imaginaries, online doubt communities, entertainment habits, and fragmented attention can reshape belief, practice, belonging, and trust in church authority. The study aims to construct a counseling model that is theologically responsible, psychologically informed, and pastorally usable in local churches. Using a conceptual qualitative design, the article synthesizes literature from digital religion studies, mediatization theory, adolescent and emerging-adult religiosity, media psychology, religious coping, and spiritually integrated counseling. The analysis identifies three main findings. First, faith degradation should be diagnosed as a layered process involving cognitive doubt, affective dryness, moral dissonance, ritual discontinuity, and communal displacement. Second, pastoral counseling must move beyond prohibition toward discerning digital habits, rebuilding spiritual attention, and restoring relational trust. Third, an integrated strategy is proposed: assessment of digital-spiritual formation, narrative and theological reconstruction, communal re-embedding, and digital rule-of-life practices. The article concludes that pastoral counseling in the digital age should function as a ministry of interpretive accompaniment rather than merely corrective instruction.